2022
DOI: 10.1101/2022.11.18.516922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cystatin F(Cst7)drives sex-dependent changes in microglia in an amyloid-driven model of Alzheimer’s Disease

Abstract: Microglial endolysosomal (dys)function is strongly implicated in neurodegeneration. Transcriptomic studies show that a microglial state characterised by a set of genes involved in endolysosomal function is induced in both mouse Alzheimer's Disease (AD) models and in human AD brain and that the onset of this state is emphasized in females.Cst7(encoding protein Cystatin F) is among the most highly upregulated genes in these microglia. However, despite such striking and robust upregulation, the sex-specific funct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Second, sex differences exist in clinical AD, and preclinical model animals also exhibit sexual dimorphisms in AD-like behaviours. In particular, Daniels MJD et al recently reported that cystatin F plays a sexually dimorphic role in regulating microglia in Cst7-deficient AD mice and that the microglia of female mice have a greater Aβ burden in vivo [77]. To avoid the potential confounding effects of sex, only male mice were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, sex differences exist in clinical AD, and preclinical model animals also exhibit sexual dimorphisms in AD-like behaviours. In particular, Daniels MJD et al recently reported that cystatin F plays a sexually dimorphic role in regulating microglia in Cst7-deficient AD mice and that the microglia of female mice have a greater Aβ burden in vivo [77]. To avoid the potential confounding effects of sex, only male mice were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cst7 is a marker of the DAM/ARM/MGnD phenotype (18, 49, 50) and involved in endolysosomal processing through inhibition of cysteine proteases (i.e., cathepsin L and C) (56). Interestingly, Cst7 knockout had sexually divergent effects on microglia in the APP NL-G-F mouse model of AD (57). Specifically, Cst7 knockout in APP NL-G-F mice led to upregulation of endolysosomal genes in females and downregulation of inflammatory genes in males.…”
Section: Discussionmentioning
confidence: 99%